Antisipasi hukum Islam dalam menjawab problematika kontemporer (kajian terhadap pemikiran maslahah mursalah al-Ghazali) - Masadah, Masadah (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2016)
The article below traces how Islamic law anticipates occurring of contemporer problematics according to Ghazali’s Maslahah Mursalah thought. According al-Ghazali, Maslahah Mursalah can be made as an argument for Islamic law determining if it fulfils many requirements: maslahat is suitable with syara’, maslahat is not contrary with al-Qur’an, as-Sunnah, and ijma, and maslahat is existing in daruriyat level or hajiyat that in same level with daruriyat. Maslahah mursalah is not independent dalil that stand alone from al-Qur’an, as-Sunnah, and Ijma’, but it is one of Islamic law istimbat methode. In other word, maslahah mursalah is not resource of Islamic law but methode of Islamic law discovering. Assembling of maslahah mursalah as dalil for Islamic law determining, it makes many moslems contemporer problematics can be known and determined although their law status not mentioned in al-Qur’an and as-Sunnah. So, maslahah mursalah assembling makes Islamic law always appropriate whenever and wherever.